"My Sad Face": An Interpersonal Metafunction Analysis of the Dialogue Between Nehemiah, Son of Hakaliah, and Artaxerxes, King of Persia, in Nehemiah 2, 2-8. Issue 2 (2nd July 2020) - Dyck, Andrew W.
ABSTRACT: In this paper, I define and apply M. Halliday's interpersonal metafunction methodology, a socio-linguistic approach to language known as Systemic Functional Linguistics, to an analysis of the dialogue between Nehemiah, son of Hakaliah, and Artaxerxes, King of Persia, in Neh 2, 2-8. My purpose is to discover some truths concerning the social dynamics that exist between Nehemiah and Artaxerxes to inevitably uncover who, that being the governing discourse participant, is responsible for and/or holds in his control Judah's restoration. To accomplish this task, I conduct both a mirco- and macro-level analysis of the designated corpus. In the end, the data reveals that Artaxerxes is the governing discourse participant though Nehemiah dominates the discourse by saying more. However, taking the greater co-text and context of Nehemiah into consideration, specifically Nehemiah's prayer of chapter 1, there is potentially a third unmentioned discourse participant who could well be the one governing the result of the present dialogue. This unmentioned discourse participant is invariably Yahweh .